Sulvanite Compounds Cu3TMS4 (TM = V, Nb and Ta): Elastic, Electronic, Optical and Thermal Properties using First-principles Method - Ali, M. A.; Jahan, N.; Islam, A. K. M. A. (Journal of Scientific Research, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> We present a systematic first-principles study of the structural, elastic, electronic, optical and thermodynamics properties of the sulvanite compounds Cu3TMS4 (TM = V, Nb and Ta). The structural, elastic and electronic properties are in fact revisited using a different calculation code than that used by other workers and the results are compared. The band gaps are found to be 1.041, 1.667 and 1.815 eV for Cu3VS4, Cu3NbS4 and Cu3TaS4, respectively which are comparable to other available calculated results. The optical properties such as dielectric function, refractive index, photoconductivity, absorption coefficients, reflectivity and loss function have been calculated for the first time. The calculated results are compared with the limited measured data on energy dependent refractive index and reflectivity coefficient available only for Cu3TaS4. All the materials are dielectric, transparent in the visible range. The values of plasma frequencies are found to be 15.36, 15.58 and 15.64 eV for Cu3VS4, Cu3NbS4 and Cu3TaS4, respectively. Furthermore, following the quasi-harmonic Debye model, the temperature effect on the bulk modulus, heat capacity, and Debye temperature is calculated reflecting the anharmonic phonon effects and these are compared with both experimental and other theoretical data where available. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i3.19191 J. Sci. Res. 6 (3), 407-419 (2014)<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; –> <!–[endif] –>